(Adv. Mater. 52/2022). Issue 52 (28th December 2022) - Unknown
Abstract : Huazhong University of Science and Technology This special issue is dedicated to the 70th Anniversary of Huazhong University of Science and Technology (HUST). The articles are contributed by the faculty of HUST, covering a broad scope of research areas in materials science, including electronic and optoelectronic materials, energy‐storage materials, materials for energy conversion and catalysis, functional soft materials, bio/medical materials, as well as advanced materials manufacturing and processing, etc. This issue offers a window representing the cutting‐edge research activities on materials at HUST.